Modular Distance Learning: Its Effect in the Academic Performance of Learners in the New Normal - Janina Molina Dargo; Michelle Dimas (STKIP Singkawang, 2021)
Due to Covid-19 pandemic, schools, particularly in the rural areas employed Modular Distance Learning (MDL) to ensure education continuity. This study seeks to investigate the effects of MDL in the academic performance of learners whether there is a significant difference in their performance before and after the implementation of MDL. Mixed method was applied in this study; Quantitative using T-Test to compare the GWA of learners and Qualitative through the use of semi-structured interview to find out the perceived effect of MDL to 15 parents, 10 learners, and 7 teachers and their recommendations. The study revealed that the 2.25% decrease in the GWA of learners after the implementation of MDL denotes a significant difference in their academic performance. MDL strengthens family bonding, independent learning, and is cost-effective. However, it is an additional workload to working parents, there is limited teacher-learner interaction, learners lack socialization with other children and have no exposure to significant school activities but are rather exposed to many distractions at home. To bridge the gaps, simplifying of modules accompanied by video lessons and audio recordings, conduct of online mediations, neighborhood instruction and home visitations are recommended. The results of this study will help teachers reflect on their current teaching strategies and improve learning outcomes. Future researchers who will conduct research related to Modular Distance Learning may also consider the findings of this study in drafting their related concepts.